Strange sisters the art of lesbian pulp fiction, 1949-1969 - Zimet, Jaye (Viking Studio, 1999)
A vivid, sexy, and titillating journey into the steamy underworld of the dime novel. In the scandalous world of pulp fiction in the 1950s and into the 60s, detectives, gangsters, and mad doctors were joined on the racks by bad girls, dissolute youths, drug-crazed beatniks, and other assorted miscreants and misfits. Where romance met with soft porn there was also a surprisingly large population of butch brunettes pursuing and seducing blond femmes. This was an alternate universe of erotic pulp fiction where gals and dolls were exploring the illicit pleasures of lesbian love--much to the delight of a largely male, heterosexual readership. Before the sexual revolution of the 1960s, these books offered a thrilling peek into the deviant underworld of wild passion and scandalous sex. Strange Sisters is a collection of the cover art of these wildly wicked novels. The women who writhe across the covers of books such as Strange Lust ("She Wanted a Woman--Then She Met Another Woman Obsessed by the Same Burning Hunger") and Women's Barracks ("The Frank Autobiography of a French Girl Soldier") sizzle with sexual energy and freedom--in a high-camp defiance of the prudish, conservative 1950s. Bold, kitschy-colorful, and fraught with sexual tension, the covers of Strange Sisters are a siren call to the retro-groovin' man, or woman, in your life.
Keywords: 1900-1999; 1950-1959; 1960-1969; amériques; corps; fiction; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques